Validity of the SPEx sports injury surveillance system for time-loss and medical attention injuries in sports - Møller, M.; Wedderkopp, N.; Myklebust, G.; Lind, M.; Sorensen, H.; Hebert, J. J.; Emery, C. A.; Attermann, J. (Scandinavian Journal of Medicine & Science in Sports, 2018)
The accurate measurement of sport exposure time and injury occurrence is key to effective injury prevention and management. Current measures are limited by their inability to identify all types of sport-related injury, narrow scope of injury information, or lack the perspective of the injured athlete. The aims of the study were to evaluate the proportion of injuries and the agreement between sport exposures reported by the SMS messaging and follow-up telephone part of the SMS, Phone, and medical staff Examination (SPEx) sports injury surveillance system when compared to measures obtained by trained on-field observers and medical staff (comparison method).